Primary healthcare for the Indian LGBTQ community – A call for inclusion. Issue 4 (2nd October 2022) - Majumder, Sunrit; Kar, Anindya
Abstract: For years now, the Indian healthcare system has been viewed through the lens of heteronormativity, sidelining sexual and gender minorities. Despite the lack of established data, an estimated 45.4 million people in India belong to the LGBTQ community and these individuals face increased risk of various physical and mental health disorders. Given the rapidly changing sexual demographic of the country, along with the changes of legislation and other factors that mold it, this paper systemically reviews LGBTQ individuals vulnerabilities toward various communicable and non-communicable diseases along with the lacunae in the primary healthcare system and the need for their inclusion in it.